PENGARUH PENGETAHUAN KESEHATAN TUBUH TERHADAP PERILAKU MAKAN SEHAT PESERTA SENAM SANGGAR JULIE - Mardiana Rahmadilla; Eti Herawati; Lilis Jubaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Body health knowledge is one of the factors that may influence an individual's healthy eating behavior. This study aimed to determine the effect of body health knowledge on the healthy eating behavior of participants at Sanggar Julie Aerobics Studio. This study employed a quantitative research design using a survey method with a cross-sectional approach. The sample consisted of 52 active aerobics participants selected through simple random sampling. The research instruments included a 19-item multiple-choice test to measure body health knowledge and an 11-item healthy eating behavior questionnaire using a Likert scale. Both instruments met the validity and reliability requirements. Data were analyzed using descriptive statistics, normality test, linearity test, heteroscedasticity test, simple linear regression analysis, partial t-test, and the coefficient of determination (R²). The results showed that there was no significant effect of body health knowledge on the healthy eating behavior of Sanggar Julie aerobics participants. This finding was indicated by a calculated t-value of 1.908, which was lower than the t-table value of 2.009, and a significance value of 0.062 (p > 0.05). The coefficient of determination (R²) was 0.068, indicating that body health knowledge explained 6.8% of the variance in healthy eating behavior, while the remaining 93.2% was influenced by other factors not examined in this study. Therefore, it can be concluded that body health knowledge does not have a significant effect on the healthy eating behavior of Sanggar Julie aerobics participants.